A REVIEW STUDY: SOCIAL MEDIA–BASED MARKETING STRATEGIES FOR BUILDING BRAND ENGAGEMENT IN THE DIGITAL ERA - Setiyo Descanandha, Rorenza; Naila Wahidah, Imro’atun (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2024)
Social media has become one of the most effective marketing channels in building relationships between brands and consumers. This review study aims to examine social media–based marketing strategies in the context of building brand engagement. The study reviews theories, practices, and previous research discussing consumer interaction, digital content, and the role of social media in strengthening brand engagement. Using a systematic literature review approach, this research analyzes academic literature from 2013 to 2024. The findings indicate that brand engagement is influenced by relevant content, interactivity, brand authenticity, and social value developed through digital communities. This study provides theoretical and practical implications for both scholars and practitioners in designing effective and relationship-oriented social media marketing strategies.